Primed and prejudiced: the Kurantha-Bothata study - Souza Junior, Luiz Carlos Victorino de (2011)
The peer review system is a core tenet of scientific publishing, as it intends to select the studies that advance knowledge. However, there have been questions concerning biases in peer review. One example amongst many is given by the essay 'Lost science in the third world' (GIBBS, 1995), which argues that there is serious bias concerning an author's address. Though there is some empirical evidence to back this statement, our knowledge of such biases, however, is limited, as few controlled studies have been provided in the literature. In this work, we have conducted an experiment, in which subjects were assigned the task of reviewing a manuscript lacking any author identification, except for a small footnote acknowledging financial support from an agency that does not exist. Under one condition, the funding agency's name is associated with the African continent, while on another condition, the agency's name is associated with the European continent. Our experiments do provide some support for the author's-bias-hypothesis.